Policy on Providing Compensation for Fixed-Term Work Agreements (Pkwt) Based on the Job Creation Law - Novyaningsih, Eka Suprihatin Ernie; Arpangi, Arpangi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The purpose of this study is to determine and analyze the compensation policy for Fixed-Term Employment Agreements (PKWT) based on the Job Creation Law. To determine and analyze the implementation of Fixed-Term Employment Agreements (PKWT) after the Job Creation Law came into effect. The approach method used by the researcher is the case approach and the statutory regulatory approach. The type of research used is normative juridical. The data sources in this study are secondary data obtained from literature studies related to the theory of legal protection and the theory of legal certainty. Based on the results of the study, the Compensation Policy for Fixed-Term Employment Agreements (PKWT) based on the Job Creation Law states that in providing compensation money, employers are required to provide compensation money to PKWT workers who have a work period of at least 1 (one) month continuously. Workers/laborers should have the same right to compensation money without discrimination. The calculation of the amount and amount of compensation funds that can be provided has been regulated in Government Regulation Number 35 of 2021 Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Time, and Termination of Employment. The implementation of Fixed Term Employment Agreements (PKWT) after the Job Creation Law came into effect still faces several challenges, such as: unclear regulations, rushed implementation, freedom to determine the term of the employment agreement, compensation regulations that do not fully provide benefits to workers.